Metal-catalyst-free gas-phase synthesis of long-chain hydrocarbons - Martínez, Lidia; Merino, Pablo; Santoro, Gonzalo; Martínez, José I; Katsanoulis, Stergios; Ault, Jesse; Mayoral, Álvaro; Vázquez, Luis; Accolla, Mario; Dazzi, Alexandre; Mathurin, Jeremie; Borondics, Ferenc; et al. (Nature communications, 2021)
Development of sustainable processes for hydrocarbons synthesis is a fundamental challenge in chemistry since these are of unquestionable importance for the production of many essential synthetic chemicals, materials and carbon-based fuels. Current industrial processes rely on non-abundant metal catalysts, temperatures of hundreds of Celsius and pressures of tens of bars. We propose an alternative gas phase process under mild reaction conditions using only atomic carbon, molecular hydrogen and an inert carrier gas. We demonstrate that the presence of CH2 and H radicals leads to efficient C-C chain growth, producing micron-length fibres of unbranched alkanes with an average length distribution between C23-C33. Ab-initio calculations uncover a thermodynamically favourable methylene coupling process on the surface of carbonaceous nanoparticles, which is kinematically facilitated by a trap-and-release mechanism of the reactants and nanoparticles that is confirmed by a steady incompressible flow simulation. This work could lead to future alternative sustainable synthetic routes to critical alkane-based chemicals or fuels.